Spinal cord stimulation modulates descending pain inhibition and temporal summation of pricking pain in patients with neuropathic pain - Schuh-Hofer, Sigrid; Fischer, Janina; Unterberg, Andreas; Treede, Rolf-Detlef; Ahmadi, Rezvan (Acta neurochirurgica, 2018)
BackgroundSpinal cord stimulation (SCS) is an established treatment option for patients with refractory chronic pain conditions. While effects of SCS on dorsal horn neuronal circuitries are intensively studied, current knowledge on the impact of SCS on descending pain pathways is scarce and relies on preclinical data. We aimed to address this topic and hypothesized a significant effect of SCS on descending pain modulation. In light of current efforts to determine the sensitivity of “static” versus “dynamic” somatosensory parameters to characterize pathophysiological pain conditions, all SCS patients were carefully investigated using both classes of somatosensory outcome parameters.MethodsDescending pain pathways were investigated by using a “Cold Pressor Test.” This test enables to evaluate the efficacy of conditioned pain modulation (CPM) at the individual level. CPM efficacy was assessed in eight neuropathic pain patients (age 55.5 ± 10.6) during the two conditions stimulator “ON” and “OFF.” The impact of SCS on “static” and “dynamic” somatosensory parameters was explored by using a quantitative sensory testing (QST) battery.ResultsCPM efficacy on pressure pain sensitivity was nearly absent during “OFF” (− 1.2 ± 5.6% facilitation), but increased significantly to 16.3 ± 3.4% inhibition during “ON” (p = 0.03). While most “static” nociceptive QST parameters, represented by mechanical/thermal pain thresholds, exhibited only small effects of SCS (p > 0.05), the wind-up ratio was strongly reduced to within the normal range during “ON” (p = 0.04; Cohen’s d = 1.0). Dynamic mechanical allodynia was abolished in six of seven patients.ConclusionsOur study provides first human evidence for an impact of SCS on descending pain pathways in the dorsolateral funiculus and emphasizes the significance of “dynamic” pain measures like “CPM”-efficacy and “temporal summation” to evaluate SCS treatment effects. Future prospective studies may use these measures of nociceptive processing to predict SCS therapy response.
Gesehen am 27.08.2019